Social Media Marketing for the Growth of an Organization in the 21st Century (Global Journal of Management and Business Research, 2019)
Social media marketing is being taken very enthusiastically by firms as a new tool in addition to traditional marketing activities. Using social media for marketing provides many advantages as cost efficiency, collaboration as well as outstanding customer management for making the firm perform better. It also has some problems like increase in employee engagement, customer traffic and competition in the online platform. The paper is secondary data based. It basically discusses the need to use social media as a marketing tool as it is mandatory to adopt new technologies to maintain brand image and customer involvement.
Keywords: social media marketing; web; 20; facebook; twitter; youtube